Appropriate ICT as a Tool to Increase Effectiveness in ICT4D: Theoreti cal considerations and illustrating cases - Reijswoud, Victor van (The Electronic Journal of Information Systems in Developing Countries, 2009)
The need to bridge the digital divide is no longer a point of discussi on and therefore focus has shifted to the design and implementation of programs that have the potential to close the information and knowled ge gap between the developing and developed nations. Unfortunately, th e majority of these programs are small and mimic what has been success ful in the developed world. It has become increasingly clear that thes e successes do not necessarily translate well in the context of develo ping nations. This paper develops the hypothesis that Information and Communication Technology (ICT) projects in developing countries will b ecome successful only when they are adapted to local conditions. The g eneral concept of Appropriate Technology (AT) will be explored for the field of ICT. AT has already been embraced by fields like architectur e, building technology and agriculture, but has not yet been rooted in ICT. The paper proposes a preliminary theory of Appropriate ICT along the lines of existing theories in AT and System development. The theo ry identifies Appropriate Technology principles at three levels: hardw are, software and ICT change management. By means of real life mini ca ses in the ICT for Development context in Africa, the guiding principl es for Appropriate ICT are illustrated. The paper will conclude with a n agenda for further research in the three identified levels. The rese arch agenda targets academia, governments, NGO's and industry.
Keywords: IMPORTANT